JQuery mobile web development essentials : learn to use the touch-optimized, cross-device, cross-platform jQM web framework for smartphones and tablets /: learn to use the touch-optimized, cross-device, cross-platform jQM web framework for smartphones and tablets. (2012) - Unknown
No abstract available